2005
DOI: 10.1080/07313830500236168
|View full text |Cite
|
Sign up to set email alerts
|

Comments on the Natural Expression and Artificial Extraction of Venom Gland Components from Spiders

Abstract: Milking or gland extraction can be used to harvest mRNA, toxins, and other materials from spiders that are suitable for a wide variety of studies, but the milked venom and extracts should not be assumed to be equivalent to naturally expressed venoms injected into insects. A much better understanding of the diverse anatomies, physiologies, and dispersion mechanisms is required for this understanding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Third, electrical milking may damage the venom glands or venom gland musculature, as proposed by other investigators. Among spiders, Argiope bruennichi failed to yield venom after a single milking (Friedel and Nentwig, 1989), and volume yield declined with additional milkings of Agelenopsis aperta (Kristensen, 2005). Sissom et al (1990) suggested that scorpions can only be milked, on average, four times before the muscles of the gland stop responding to electrical stimulation.…”
Section: -Month Follow-up Studymentioning
confidence: 97%
See 1 more Smart Citation
“…Third, electrical milking may damage the venom glands or venom gland musculature, as proposed by other investigators. Among spiders, Argiope bruennichi failed to yield venom after a single milking (Friedel and Nentwig, 1989), and volume yield declined with additional milkings of Agelenopsis aperta (Kristensen, 2005). Sissom et al (1990) suggested that scorpions can only be milked, on average, four times before the muscles of the gland stop responding to electrical stimulation.…”
Section: -Month Follow-up Studymentioning
confidence: 97%
“…Thus, further testing would be necessary to better understand how toxicity changes during venom regeneration. Even so, protein content of venom can vary with extraction method (Mackessy, 2002;Brochetto-Braga et al, 2006;Oukkache et al, 2013), and venom elicited by electrical milking cannot be assumed to be identical in composition to that used during natural prey capture or defense (Kristensen, 2005).…”
Section: Functional Aspects Of Venom Regenerationmentioning
confidence: 99%